Pengaruh Kecerdasan Spiritual Dan Kecerdasan Emosional Terhadap Kinerja Pegawai Melalui Komitmen Organisasi Sebagai Variabel Intervening Di Badan Keuangan Daerah (Bkd) Dharmasraya - Ishan, Dio; Sari, Marta Widian; Sari, Yosi Puspita (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to determine the extent of the influence of spiritual intelligence and emotional intelligence on employee performance through organizational commitment as an intervening variable at the Regional Finance Agency (BKD) of Dharmasraya Regency. The research method used is a quantitative method with data collection techniques through questionnaire surveys. The population in this study were all 52 employees of BKD Dharmasraya. Given the relatively small population size, the sampling technique used saturated sampling (census), so the entire population was used as a sample. Data analysis was performed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the help of SmartPLS 3.0 software. The results showed that: (1) Spiritual intelligence has a positive and significant effect on organizational commitment; (2) Emotional intelligence has a positive and significant effect on organizational commitment; (3) Spiritual intelligence has a positive and significant effect on employee performance; (4) Emotional intelligence has no significant effect on employee performance directly; (5) Organizational commitment has a positive and significant effect on employee performance; (6) Organizational commitment mediates the effect of spiritual intelligence on employee performance; and (7) Organizational commitment mediates the effect of emotional intelligence on employee performance. These findings indicate that organizational commitment plays a vital role in improving performance, especially in bridging the influence of emotional intelligence